NCOA4-mediated ferritinophagy in macrophages is crucial to sustain erythropoiesis in mice - Nai, Antonella (Haematologica, 2020)
Nuclear receptor coactivator 4 (NCOA4) promotes ferritin degradation and Ncoa4-ko mice in a C57BL/6 background show microcytosis and mild anemia, aggravated by iron deficiency. To understand tissue-specific contributions of NCOA4-mediated ferritinophagy we explored the effect of Ncoa4 genetic ablation in the iron-rich Sv129/J strain. Increased body iron content protects these mice from anemia and, in basal conditions, Sv129/J Ncoa4-ko mice show only microcytosis; nevertheless, when fed a low-iron diet they develop a more severe anemia compared to that of wild-type animals. Reciprocal bone marrow (BM) transplantation from wild-type donors into Ncoa4-ko and from Ncoa4-ko into wild-type mice revealed that microcytosis and susceptibility to iron deficiency anemia depend on BM-derived cells. Reconstitution of erythropoiesis with normalization of red blood count and hemoglobin concentration occurred at the same rate in transplanted animals independently of the genotype. Importantly, NCOA4 loss did not affect terminal erythropoiesis in iron deficiency, both in total and specific BM Ncoa4-ko animals compared to controls. On the contrary, upon a low iron diet, spleen from wild-type animals with Ncoa4-ko BM displayed marked iron retention compared to (wild-type BM) controls, indicating defective macrophage iron release in the former. Thus, erythropoietin administration failed to mobilize iron from stores in Ncoa4-ko animals. Furthermore, Ncoa4 inactivation in thalassemic mice did not worsen the hematologic phenotype. Overall our data reveal a major role for NCOA4-mediated ferritinophagy in macrophages to favor iron release for erythropoiesis, especially in iron deficiency.